– Arabic, English, Turkish vowels – comparative studying - Nouafla, Mahmoud Rajaa Hassan (Arab Journal for Sciences and Research Publishing, 2018)
This study aims to investigate the characteristics of Turkish vowel sounds, contrast them with Arabic vowel sounds and show similarities and differences between the vowel sounds of the two languages by testing them against the International Cardinal Vowels System which is a system designed by Daniel Jones to describe English vowels. Therefore, the research must test Arabic and Turkish The study reveals many drawbacks for considering English as the grounds on which measuring is carried out. This is due to the fact that English is not a phonetic language there is no conformity between what is spoken and what is written in many aspects.To investigate this, the study starts with an introduction, which highlights the peculiarities of the Turkish language in the harmony of its sounds, and its uniqueness in the presence of written symbols for vowel sounds in both forms: emphatic and non emphatic.three headlines discuss the similarities and differences between Arabic and Turkish in terms of emphatics and non- emphatics, vowel lengthening, deletion, metathesis, shortening vowels, and syllable structure of these languages.The conclusion shows the need for a new international cardinal vowel system. It also contains a practical result based on the findings of the research. Then, a list of sources and references follows
Keywords: Vowel sounds; standard vowel system; Daniel Jones; consonant; weak